Saying Goodbye to Mariposa: Robertson Davies’s Deptford and the Small-Town Convention - Porter, Ryan (Studies in Canadian Literature, 2011)
In Sunshine Sketches of a Little Town (1912), Stephen Leacock’s Mariposa is paradigmatic of a type of small-town fiction with which many subsequent texts such as Robertson Davies’s Fifth Business (1970) are in conversation. Davies’s Deptford is simultaneously a product and a rejection of Mariposa’s influence. Through a process of escape and self-discovery, Dunstan Ramsay must negotiate the residue of his Deptford past with his evolving present, and this process helps to reveal how the small-town convention emerges. An initial focus on Dunstan’s sincere attempts at accurately rendering his village enables an exploration of the broader connotations of his explicit knowledge of, temporary reliance on, and eventual abandonment of a small-town archetype epitomized by Mariposa. If Leacock’s town is read as a home place of Canadian fiction and cultural identity, then Fifth Business draws attention to the mode of memory responsible for that type of exegesis. If Mariposa is the past perfect, then Deptford is the past progressive.